2012
DOI: 10.1038/ncomms2014
|View full text |Cite
|
Sign up to set email alerts
|

Organellar mechanosensitive channels in fission yeast regulate the hypo-osmotic shock response

Abstract: A key molecule of sensing machineries essential for survival upon hypo-osmotic shock is the mechanosensitive channel. The bacterial mechanosensitive channel mscs functions directly for this purpose by releasing cytoplasmic solutes out of the cell, whereas plant mscs homologues are found to function in chloroplast organization. Here we show that the fission yeast mscs homologues, designated msy1 and msy2, participate in the hypo-osmotic shock response by a mechanism different from that operated by the bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
86
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(92 citation statements)
references
References 47 publications
5
86
1
Order By: Relevance
“…E. coli MscS is among the smallest members of its eponymous family of proteins, and deletion studies indicate that it contains little nonessential protein sequence (Miller et al, 2003b;Schumann et al, 2004). However, other MscS family members show substantial variation in size and topology, containing anywhere from 3 to 12 TM helices ) and a variety of domains not found in MscS, such as large cytoplasmic loops, N-or C-terminal extensions, extracellular domains, and ion or cyclic nucleotide binding motifs (Li et al, 2002(Li et al, , 2007Haswell et al, 2011;Malcolm and Maurer, 2012;Nakayama et al, 2012;Wilson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…E. coli MscS is among the smallest members of its eponymous family of proteins, and deletion studies indicate that it contains little nonessential protein sequence (Miller et al, 2003b;Schumann et al, 2004). However, other MscS family members show substantial variation in size and topology, containing anywhere from 3 to 12 TM helices ) and a variety of domains not found in MscS, such as large cytoplasmic loops, N-or C-terminal extensions, extracellular domains, and ion or cyclic nucleotide binding motifs (Li et al, 2002(Li et al, , 2007Haswell et al, 2011;Malcolm and Maurer, 2012;Nakayama et al, 2012;Wilson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Homologs of MscS are found in nearly all bacterial species (Pivetti et al, 2003;Lai et al, 2013;Martinac et al, 2013), protozoa (Prole and Taylor, 2013), archaea (Palmieri et al, 2009), some fungi (Nakayama et al, 2012), and all plant genomes so far analyzed (Wilson et al, 2013) but have not been identified in animals. The region of sequence similarity between MscS and other members of the MscS superfamily is restricted to a relatively small portion of the protein that includes the pore-lining helix of MscS and ;100 amino acids of the upper cytoplasmic domain (Kloda and Martinac, 2002;Pivetti et al, 2003;Balleza and Gómez-Lagunas, 2009;Haswell et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations